Performance Analysis on UWB Antennas for Breast Cancer Detection - V. Vijayasarveswari; M. Jusoh; T. Sabapathy; S. Khatun (Advanced Aspects of Engineering Research Vol. 2, 2021)
Breast cancer is a common disease among women and death figure is continuing to increase. As there is no remedy in the late stage, early breast cancer detection is crucial. Ultra wide-band (UWB) is the promising candidate for its specificity and lack of ionizing radiation. This chapter presents the performance analysis of different types of UWB antennas for breast cancer detection. The antennas’ performance is compared based on the accuracy obtained from the neural network (NN) module for each UWB antennas. Three types of antennas which are taken into the account are UWB patch, UWB pyramidal and UWB horn antennas. UWB signals are transmitted from one antenna and received by another antenna. Both forward and backward scattered UWB signals are collected. The collected signals are fed into developed NN module to measure the performance accuracy of each antenna. UWB pyramidal antenna (90.55%) performs better compared to UWB horn (87.11%) and UWB patch (83.14%) antennas for both signal scattered methods. Backward scattered method (89.17%) achieves better accuracy for detection compare to forward scattered method (84.69). These results indeed give us the assurance of early breast cancer detection and save precious lives.